Supervisor’s Negative Mood and Healthcare Workers’ Voice Behavior: A Moderated Mediation Model - Yuan, Ping; Cheng, Yuan; Liu, Yanbin; Liu, Shifeng (Frontiers in Psychology, 2022)
Healthcare workers' voice is of importance in decreasing medical accidents and improving the efficacy of hospital units. To investigate the impact and the underlying mechanisms of supervisors’ negative mood on healthcare workers’ voice behavior, based on the mood contagion perspective, we designed a cross-sectional study, with 299 healthcare workers from mainland China completed the questionnaires. The results indicated supervisors’ negative mood was positively related to healthcare workers’ negative mood, which further led to less constructive voice and more defensive voice. Moreover, the healthcare worker’s emotional intelligence aspect of self-emotion appraisal moderated this relationship, but not others-emotion appraisal. We believe healthcare workers’ supervisors should pay attention to their negative mood expression and regulation. In the hope of reducing being influenced by supervisors’ negative mood, training about noticing and recognizing their own emotions are needed for healthcare workers.